Prevalence of ancylostomiasis in people living in slum area, Philhousepet of Eluru, West Godavari District (Andhra Pradesh) - Indira, R. (Springer-Verlag, 2012)
Hookworm infection was found in the slum area of Eluru, West Godavari District, A.P. which has scheduled caste population. Infection is related to different climatic conditions and socio-economic status of the population. The inhabitants are coolies in agricultural fields and household workers with a poor level of hygiene and sanitation. All the infected positive cases showed Ancylostoma duodenale infection. The prevalence of hookworm infection was 15.6, 17.9 and 14 % in children, 23.5, 27.9 and 20.5 % in adults during summer, rainy and winter seasons respectively. Single species infection was studied in three periods. Out of 264 faecal samples, 128 children (40 males, 32.5 %) and 136 adults (64 men, 25 % and 72 women, 30.5 %) showed helminthic infection in rainy season. Much variation is seen in the prevalence of disease in rainy and winter seasons in all the age groups. The infected individuals were treated with albendazole just after rainy season. Three weeks after antihelminthic treatment, the infection rate among them was lowered; health education also plays a role in reducing the % of infection.